Strategi Guru dalam Mengembangkan Kemandirian Anak melalui Metode Montessori di TK Islam Al-Fitriyah - Tin Surtini; Nandiya Sri Pertiwi; Siti aisyah; Saadah, Saadah; Cecep Hilman (Yayasan Literasi Sains Indonesia, 2025)
Early childhood independence is a crucial aspect of their development, especially in formal educational environments such as kindergartens. This study aims to analyze teachers' strategies in fostering children's independence through the Montessori method at TK Islam Al-Fitriyah Sukabumi. This research employs a qualitative approach with a descriptive study design. Primary data were obtained through interviews with the principal and teachers, as well as direct observations. Meanwhile, secondary data were collected through document studies related to the implementation of the Montessori method in the school. The data analysis techniques used in this study include data reduction, data presentation, and conclusion drawing. The results indicate that teachers' strategies in fostering children's independence include providing structured freedom, utilizing Montessori learning materials, and offering individualized guidance according to each child's needs. The findings reveal that the Montessori method is effective in enhancing children's independence, particularly in decision-making, motor skills, and self-discipline. The study concludes that the proper implementation of the Montessori method with appropriate strategies can help children become more independent in both learning activities and daily life.